Seizure-Induced Motility of Differentiated Dentate Granule Cells Is Prevented by the Central Reelin Fragment - Orcinha, Catarina; Münzner, Gert; Gerlach, Johannes; Kilias, Antje; Follo, Marie; Egert, Ulrich; Haas, Carola A. (Frontiers in Cellular Neuroscience, 2016)
Granule cell dispersion (GCD) represents a pathological widening of the granule cell layer in the dentate gyrus and it is frequently observed in patients with mesial temporal lobe epilepsy (MTLE). Recent studies in human MTLE specimens and in animal epilepsy models have shown that a decreased expression and functional inactivation of the extracellular matrix protein Reelin correlates with GCD formation, but causal evidence is still lacking. Here, we used unilateral kainate (KA) injection into the mouse hippocampus, an established MTLE animal model, to precisely map the loss of reelin mRNA-synthesizing neurons in relation to GCD along the septotemporal axis of the epileptic hippocampus. We show that reelin mRNA-producing neurons are mainly lost in the hilus and that this loss precisely correlates with the occurrence of GCD. To monitor GCD formation in real time, we used organotypic hippocampal slice cultures (OHSCs) prepared from mice which express enhanced green fluorescent protein (eGFP) primarily in differentiated dentate granule cells. Using life cell microscopy we observed that increasing doses of KA resulted in an enhanced motility of eGFP-positive granule cells. Moreover, KA treatment of OHSC resulted in a rapid loss of Reelin-producing interneurons mainly in the hilus, as observed in vivo. A detailed analysis of the migration behavior of individual eGFP-positive granule cells revealed that the majority of these neurons actively migrate toward the hilar region, where Reelin-producing neurons are lost. Treatment with KA and subsequent addition of the recombinant R3–6 Reelin fragment significantly prevented the movement of eGFP-positive granule cells. Together, these findings suggest that GCD formation is indeed triggered by a loss of Reelin in hilar interneurons.